2021
DOI: 10.3389/fcvm.2021.742601
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Apelin and Atrial Fibrillation in Patients With High Risk of Ischemic Stroke

Abstract: Background: Atrial fibrillation (AF) is associated with high risk of stroke preventable by timely initiation of anticoagulation. Currently available screening tools based on ECG are not optimal due to inconvenience and high costs. Aim of this study was to study the diagnostic value of apelin for AF in patients with high risk of stroke.Methods: We designed a multicenter, matched-cohort study. The population consisted of three study groups: a healthy control group (34 patients) and two matched groups of 60 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Atrial fibrillation (AF) is associated with a high risk of stroke, and should therefore be detected in a timely manner. Bohm et al (2021) showed that apelin levels were significantly lower in stroke patients with AF compared to the non-AF group in a multicenter, matched-cohort, and only apelin was identified as an independent predictor of AF. Thus, apelin administration should be considered in patients with high risk of stroke to exclude the possibility of AF.…”
Section: Apelin-13 and Cerebral Ischemiamentioning
confidence: 94%
“…Atrial fibrillation (AF) is associated with a high risk of stroke, and should therefore be detected in a timely manner. Bohm et al (2021) showed that apelin levels were significantly lower in stroke patients with AF compared to the non-AF group in a multicenter, matched-cohort, and only apelin was identified as an independent predictor of AF. Thus, apelin administration should be considered in patients with high risk of stroke to exclude the possibility of AF.…”
Section: Apelin-13 and Cerebral Ischemiamentioning
confidence: 94%
“…Because of its role in many pathophysiological and physiological processes including oxidative stress and inflammation, apelin has been studied as a potential biomarker for several diseases including diabetes [ 79 ], atrial fibrillation [ 80 , 81 , 82 ], cancer [ 83 ], liver disease [ 84 ], and many others.…”
Section: Methods Of Lvh Detectionmentioning
confidence: 99%
“…such as a biomarker detectable in peripheral blood, would be signifi cantly benefi cial in the management of AF patients and several biomarkers have already been investigated in this context (13)(14)(15)(16)(17). Based on available literature and our prior research apelin shows promising results (18)(19)(20)(21).…”
Section: U N C O R R E C T E Dmentioning
confidence: 96%
“…Our previous research included two studies in patients with low risk of stroke and one in patients with high risk (18,19,21). In this study we pooled all patients from previous studies including previously unreported patients excluded in patient matching, forming a large heterogenous study population with a goal to further investigate apelin's predictive value for AF.…”
Section: U N C O R R E C T E Dmentioning
confidence: 99%
See 1 more Smart Citation